2021
DOI: 10.3390/app11020699
|View full text |Cite
|
Sign up to set email alerts
|

A Dual Frequency Ultrasonic Cleaning Tank Developed by Transient Dynamic Analysis

Abstract: At present, development of manufacturer’s ultrasonic cleaning tank (UCT) to match the requirements from consumers usually relies on computer simulation based on harmonic response analysis (HRA). However, this technique can only be used with single-frequency UCT. For dual frequency, the manufacturer used information from empirical experiment alongside trial-and-error methods to develop prototypes, resulting in the UCT that may not be fully efficient. Thus, lack of such a proper calculational method to develop t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(34 citation statements)
references
References 33 publications
5
29
0
Order By: Relevance
“…Ultrasonic Transducer (UT) is an electronics device that transforms electricity into vibration in the range of 20-200 kHz transmitted through media for such applications. For example, UT has been used in welding machines [1], cell disruptors [2], and cleaning machines [3][4][5][6][7]. For the cleaning purpose, UT can be divided into two types of operation: Outer Ultrasonic Transducer (OUT) and Submersible Ultrasonic Transducer (SUT), as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ultrasonic Transducer (UT) is an electronics device that transforms electricity into vibration in the range of 20-200 kHz transmitted through media for such applications. For example, UT has been used in welding machines [1], cell disruptors [2], and cleaning machines [3][4][5][6][7]. For the cleaning purpose, UT can be divided into two types of operation: Outer Ultrasonic Transducer (OUT) and Submersible Ultrasonic Transducer (SUT), as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the PZT8 has been used in devices that require higher durability than the PZT4 [17][18][19][20]. However, all mentioned technology in previous studies [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] cannot provide a satisfactory result in the industrial cleaning process. The produced cavitation still did not fully cover the industrial grade's tank even though there are several UTs installed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…After that, the results in Figure 9a would be calculated using a fast Fourier transform (FFT) and then normalized with the maximum pressure to obtain the normalized power spectrum (NPS) as in Figure 9b. This NPS could be the indicator to precisely investigate the frequency, as mentioned in [29]. From the results in Figure 9a, it was confirmed that the shapes of the modifications affected the average pressure.…”
Section: Structural Dynamicsmentioning
confidence: 53%